What Drives Crop Farmers’ Adaptation to Climate Change: Evidence from Smallholder Farmers in Kogi Agricultural Zones, Nigeria - Stephen Jimoh, Ibitoye (2020)
Prevailing scenarios in Kogi agricultural zones of Nigeria, such as; the environment becoming hotter and drier, rainy seasons getting unpredictable and increasingly erratic and different variations are clear evidence of climate change which alternate cropping date or duration, and has grown to become a major concern for sustainable agricultural production. This study determined factors that drive crop farmers’ adaptation to climate change in Kogi Agricultural Zones, Nigeria using a randomly selected one hundred and fifty (150) farmers as respondents. Relevant primary data obtained through questionnaire administration in March – June 2018 were analyzed using descriptive and inferential statistical tools. The Tobit regression model was used to determine the drivers of adaptation to climate change. The socioeconomic characteristics of the sampled respondents showed that 78.67% were males with a mean age of 40 years. The result further showed that majority of the farmers were aware of the effect of climate change (sigma score = 5.714) with respect to the following items: hot environment (sigma score = 5.300), irregular rainfall (sigma score = 5.300), and yield reduction (sigma score = 5.082). The Tobit regression result indicated that age (β = 0.028), household size (β = -0.072), membership of cooperative society (β = 0.439) and number of extension contacts (β = 0.026) were significant factors that drive smallholder crop farmers’ adaptation to climate change. For informed policy decisions; the government and other relevant stakeholders should encourage farmers to join agricultural cooperative societies and also continue to support the extension service delivery system to increase farmers’ adaptation capacities.